(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Bullying in the educational environment is one of the most pressing socio-psychological problems facing modern society. The prevalence of bullying among primary school-aged children is particularly alarming, as this is the period when the foundations of personality are laid, social skills, self-esteem, and interpersonal interaction patterns are formed. Early exposure to aggressive behavior from peers can have a long-term negative impact on a child’s mental development, emotional state, academic motivation, and social adaptation.